Tax Sanctions from the Authority Perspective - Sumuan, Cindy Fitria; Fidiana, Fidiana (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 15 No 1 (2020), 2020)
Tax sanctions are imposed by national and local tax authorities to provide a deterrent effect and encourage taxpayer compliance. This research aims to investigate the application of tax sanctions from the perspective of tax authorities. This is a qualitative research that recruited three informants from the tax authorities in the Surabaya Sawahan Tax Office. In-depth interviews comprised the data collection technique used in this research. Data analysis involved data reduction, data presentation and conclusion, and verification. Results showed that the tax sanctions in the Surabaya Sawahan Tax Office have been implemented in accordance with the legal procedures and regulations. Administrative sanctions can be applied through the issuance of tax collection letters conducted through prior research, and criminal sanctions can be imposed by the tax authorities as a last resort. Keywords : Tax sanctions; tax authorities; gijzeling; tax compliance